Selling Green Through Algorithms: How AI Advertising Shapes Eco-Conscious Consumers - Nur Fadilah Ayu Sandira (Journal of Studies in Academic, Humanities, Research, and Innovation, 2025)
This study examines the influence of AI advertising exposure, green message credibility, and digital engagement on eco-conscious consumer behavior in Indonesia. Using a quantitative approach with a survey design, data were collected from 170 active social media users who had interacted with digital advertisements containing sustainability messages and purchased environmentally friendly products online. Data analysis employed multiple linear regression using SPSS. The findings reveal that AI advertising exposure, green message credibility, and digital engagement each have a significant and positive effect on eco-conscious consumer behavior, both partially and simultaneously. The results indicate that artificial intelligence serves not merely as a promotional instrument but as a bridge connecting ecological awareness with sustainable consumption. Digital engagement emerges as the strongest predictor, demonstrating that consumers who interact more actively with green content tend to exhibit higher levels of sustainable behavioral commitment. The study contributes to the theoretical development of AI driven marketing by integrating technological personalization with ethical and participatory dimensions of sustainability communication. Practically, the findings suggest that marketers must balance algorithmic efficiency with message credibility and ethical transparency to ensure that AI-driven campaigns do not merely promote green products but cultivate long term ecological awareness and consumer trust.